2016
DOI: 10.16965/ijar.2016.467
|View full text |Cite
|
Sign up to set email alerts
|

Morhometric Study of Septomarginal Trabeculae (Moderator Band)

Abstract: Background and objectives: Septomariginal trabeculae or Moderator band is a specialized bridge connecting interventricular septum to the base of the anterior papillary muscle. It contains Right Bundle branch of HIS, it is also Known to prevent the over distension of the right ventricle. The literature review shows the paucity of articles related to morphological and morphometric evaluation. Since it has a great clinical importance its, further studies become Mandatory. Here we have measured the angle of the Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
4
6
0
Order By: Relevance
“…In our study too we have found a specimen with 1mm thickness. However in our study the thickness differs at the origin, the midpoint and at the insertion, the origin of false chordae tendinae which agrees with the Praveen Shenoy M et al study [20]. In the study of Praveen Shenoy et al [17], the mean angle got was 115° with a narrow angle of 110°-120°.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study too we have found a specimen with 1mm thickness. However in our study the thickness differs at the origin, the midpoint and at the insertion, the origin of false chordae tendinae which agrees with the Praveen Shenoy M et al study [20]. In the study of Praveen Shenoy et al [17], the mean angle got was 115° with a narrow angle of 110°-120°.…”
Section: Discussionsupporting
confidence: 88%
“…However in our study the thickness differs at the origin, the midpoint and at the insertion, the origin of false chordae tendinae which agrees with the Praveen Shenoy M et al study [20]. In the study of Praveen Shenoy et al [17], the mean angle got was 115° with a narrow angle of 110°-120°. In Raghavendra A Y et al [20] study, the mean height is found to be 36mm, but in our study it is found to be 23.2mm.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have observed many diverse forms of the MB with different lengths and widths, and several morphological classifications of the MB with several subtypes have been defined (Table 3) [134567]. The present study also found, there were several types of the MB, despite its small size.…”
Section: Discussionsupporting
confidence: 76%
“…Several anatomical studies that have investigated the shape of the MB [134567] have revealed that the MB takes various forms. It has been reported that an anomalous MB has clinical significance in the double-chamber right ventricle and in atrial and ventricular septal defects [389101112].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the location of moderator bands and the distribution of conductive cells in those structures have been conducted in humans (Bandeira et al, ; Chaudhary, Bharti, & Deshpande, ; Kosiński et al, ; Mamatha, Shenoy, D´Souza, Prasana, Sumalatha, Shenoy, D´Souza, Prasanna, & Sumalatha, ; Rocha et al, ; Shenoy, Lucas, Vinay, & Ramos, ) and several animal species, including goats (Leão et al, ), sheeps (Ansari, Ho, & Anderson, ), pigs (Bojsen‐Moller & Tranum‐Jensen, ; Gulyaeva & Roshchevskaya, ), dogs (Bombonato et al, ), equines (Bombonato et al, ; Sathyamoorthy & Ramesh, ), buffalos (Ghonimi et al, ) and ostriches (Parto, Tadjalli, & Ghazi, ). Meanwhile, not many studies involving morphology, tissue morphological composition and possible variations of the septomarginal trabecula were performed.…”
Section: Introductionmentioning
confidence: 99%